Dr. Harassment Matters: Perception of Students on Hazardity of Political, Religious, Economic, Sexual and Social Harassment in the Academia - Sambo, Bala Ibrahim (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
This study investigated the perception students have on the relative hazardity of political, religious, economic, sexual and social harassment on students. Four hundred students were drawn as research respondents through convenience and stratified sampling techniques. Using Likert type scale, respondents were requested to indicate the level of hazard of each political, religious, economic, sexual and social harassment (PRESS) factor using 5 = very hazardous; 4 = hazardous; 3 = neutral; 2 = not hazardous; 1 = less hazardous. Digital interview was used to obtain data from the respondents. Frequency counts, percentage, relative importance index and chi square were used to analyse the data. Results indicated that the PRESS factors were perceived as hazardous by students; however, contrary to popular belief that sexual harassment was most hazardous, the results indicated that religious harassment was the most hazardous; sexual harassment was second; economic harassment was third; political harassment was fourth; and social harassment was fifth. Based on the findings, it was recommended that harassment factors should be addressed according to their magnitude; and that addressing harassment behaviour should be holistic and comprehensive. Furthermore, education of stakeholders should take the issue of harassment serious by being proactive.